Changes, expectations and identity - Factors that influence retirement among - Stralman, O. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Objective The main objective of this study was to analyse factors that influence the view of former Swedish elite athletes on (a) Important adjustment factors in the sport retirement process, (b) What individual sportrelated qualities are useful in post retirement career development and (c) The respondent`s perceived loss of sport qualities. These factors will be discussed in relation to their influence on the former athlete`s identity. Methods A postal questionnaire was sent to 510 male and female former top Swedish elite athletes from different sports. After one reminder, 67 % of the questionnaires were returned (n=343). The statistical method used was factor analysis - PCA. Results / Conclusions The adjustment processes to retirement comprise qualities that are useful in post retirement career development, such as goal orientation, self-confidence and control, social ability, coping with stress and maintaining health. The data reduction procedures revealed that a sport-related identity could be both beneficial and problematic. The respondents claimed that certain sport-related abilities, social competence, adaptation resources and health factors generated positive emotions. Positive and negative emotions were influenced by the absence of sporting triggers and attributes as well as the presence of sport-related losses. The sporting identity was strengthened by the notion of being physically fit, the elite sport atmosphere, as well as by external elite sport rewards.